Kesiapan Perpustakaan Sekolah Dalam Pengembangan Koleksi Untuk Menunjang Prestasi Siswa - Miftahul Janah; Lolytasari Lolytasari; Abd. Aziz Hasibuan (UIN Mataram, 2022)
Planning a good collection development will affect the improvement of students' insight and references to get good achievements. In addition, the fulfillment of the collection will be able to translate the lessons taught by the teachers. In this case, library readiness is needed to support the school's vision and mission to improve student achievement. This study aims to determine the effect of library management on student achievement at SMA Negeri 8 Jakarta. This type of research is quantitative with a simple linear regression analysis approach. This study uses probability sampling where the population is class XI students as many as 354 students and class XII as many as 360 students so that the total population becomes 714 students. The sources of this research come from questionnaires, document studies and interviews. The results of the study found that there was a positive influence between library management and student achievement at SMA Negeri 8 Jakarta. This can be seen from the data processing of SPSS ver 22 calculation results, through statistical testing of the t test. the results of the t count value of 2,915 and t table of 1,998 with a significance of 0,005. With the test criteria t count > t table and if the significance is < (0.05), then H0 is rejected, then in the calculation of the coefficient of determination it is known that the influence of library management on student achievement at SMA Negeri 8 Jakarta is 9% while the remaining 91 percents is influenced by other factors. not researched. The readiness of libraries to increase student predation begins with developing electronic-based library collections and providing access to collections by utilizing OPAC. In addition, to improve information literacy, the library held a workshop on writing scientific papers by inviting well-known writers.